Un cammino accidentato: fonti documentali, fotografie e scrittura nella pratica della Public History - Mignemi, Adolfo (Rivista di studi di fotografia. Journal of Studies in Photography, 2017)
Public History relies on complex textual forms, in which photographs, movies, sounds, oral memories and, in small part, writing, interact with one another. Common standards of presentation for such diverse sources have not yet been defined. Furthermore, the practice of Public History often generates texts in which photographs are reproduced without any critical analysis of their internal evidence and contextual information, such as their archival history. This essay discusses some of the methodological issues and of the technical tools related to the use of photographs in Public History.